Potency of Indigenous Epiphytic Yeast to Control Colletotrichum capsici, the Cause of Anthracnose Disease in Red Chili: Potensi Khamir Epifit Indigenus untuk Mengendalikan Colletotrichum capsici, Penyebab Penyakit Antraknosa pada Buah Cabai Merah - Darnetty, Darnetty; Hermaleni, Utari; Yunisman, Yunisman (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2022)
Anthracnose is an important disease in red chili caused by Colletotrichum capsici which can reduce productivity by up to 65%. Controlling using indigenous epiphytic yeasts has never been done. The study aimed to determine the ability of indigenous epiphytic yeast isolates to control C. capsici on red chili. The study was carried out at the Phytopathology Laboratory, Faculty of Agriculture, Universitas Andalas, from August 2019 - April 2020 in vitro and in vivo. The study used a completely randomized design (CRD) which consisted of 6 treatments with five different isolates (4 isolates from fruit and one from leaves) and a control. Parameters observed were macroscopic and microscopic characteristics of yeasts, C. capsici colony area, disease incubation period, and anthracnose symptoms. The results showed that the five epiphytic yeast isolates could suppress the growth of C. capsici, inhibit colony expansion between 27.09 – 59.11%, extend the incubation period for one day, and inhibit the expansion of anthracnose symptoms between 52.30 – 62.64%. Epiphytic yeast isolate KB1 derived from fruit has the highest inhibition.